PHYSICO-CHEMICAL CHARACTERIZATION OF MACEDONIAN FORREST HONEY - Sulejmani, Erhan; Hajrulai musliu, Zehra; Uzunov, Risto (Udruženje za nutricionizam i dijetetiku „Hranom do zdravlja“ Tuzla, BiH, 2020)
The study was aimed to determine the quality of forest honey obtained from nectar of forrest plants and and to evaluate the physico-chemical properties of forest honey from Macedonia in 2019/20. For analysis forty five (45) honey samples each were obtained from various locations and compared against to the national and international standards. The physico-chemical properties evaluated were: Moisture Content, Ash, Free Acidity, Hydroxy methyl furfural, Reducing Sugars, Sucrose Content and Electric Conductivity. Though there were some significant variation (P<0.05) between the different regions, all samples collected were found in the range of the national and international standard limits. The average values of honey samples for moisture, ash, free acidity, hydroxy methyl furfural, apparent reducing sugar, sucrose and electric conductivity were: 16.65 %, 0.32 %, 24.94 meq/kg, 12.40 ppm, 69.25 g/100g, 1.77 g/100g and 0.41 mS/cm, respectively. Results obtained in this study, indicate that honeys produced in Republic of North Macedonia show excellent quality properties according to the national and international standards.
FIZIKALNO-KEMIJSKA KARAKTERIZACIJA MAKEDONSKOG ŠUMKOG MEDA
Keywords: forest honey, reducing sugar, physical properties, hydroxy methyl furfural